"Something a bit more personal": Digital storytelling and intimacy among queer Black women. (December 2020) - Adams-Santos, Dominique
Coming-out stories are important cultural texts wherein individuals articulate and interpret experiences of identifying as sexual minorities. Yet, much of the extant literature on coming-out stories examines narratives by white, middle-class gay men and lesbians. Critical inquiry into coming-out stories told by privileged queer subjects points to the formulaic and normative characteristics of their narratives, where sexual difference is downplayed or challenged. The goal of this article, then, is to ask whether and how coming-out narratives told by queer Black women conform to or depart from the "coming-out formula story." Using an intersectional approach to narrative analysis, this article investigates the performative and discursive strategies that 50 women use in telling their coming-out stories on YouTube. Findings show that queer Black women's use of intimate candor—the performative and discursive strategy of publicly revealing interior, often sexually explicit, aspects of the self—is a means through which women center desire and queerness; articulate a vision of queer Black womanhood; and complicate the coming-out formula.